Comparison of Age of Thelarche between Obese and Normal Girls - Yunitasari, Yunitasari; Fadil, R.M. Ryadi; Dwiyatnaningrum, Fenny (Althea Medical Journal, 2016)
Background: Childhood obesity has become a major concern in recent years. The increasing childhood obesity prevalence may occur as the result of food consumption with high content of calories, fat, cholesterol and the lack of physical activity. Obesity in children will also affect their pubertal development. Puberty is a period in which maturation of the reproductive function is achieved.In girls, the initial sign of puberty is thelarche, defined as the appearance of breast bud underneath the areola.The onset of puberty depends on many factors, one of them is nutritional status especially obesity. This study was conducted to compare the age of thelarche between obese and normal girls.Methods: An analytical study using cross sectional method was conducted. This study was held in Bandung, West Java, Indonesia, during the period of SeptemberïOctober 2013. Data were obtained from 3 elementary schools, selected by multistage random sampling.The total subject was 46. Data were analyzed using the Mann-Whitney and chi-square test.Results: Thelarche occurred at age 9 years 4 months in the obese group compared to 11 years 2 months in the normal group. The analysis using Mann-Whitney test showed the difference was statistically significant (p<0.001). Based on age group, 42% obese girls attained thelarche between ages 8ï9 years, while 63% girls in the normal group attained thelarche between ages 11ï12 years. The analysis using chi- square test showed that the difference was statistically significant (p<0.001).Conclusions: Thelarche occurs earlier in obese girls compared to normal girls. [AMJ.2016;3(3):411â5]DOI: 10.15850/amj.v3n3.906